Calycosin alleviates allergic contact dermatitis by repairing epithelial tight junctions via down‐regulating HIF‐1α. Issue 9 (11th July 2018) - Jia, Zhirong; Wang, Xiaotong; Wang, Xiaoyu; Wei, Pan; Li, Lianqu; Wu, Peng; Hong, Min
Abstract: Calycosin, a bioactive component derived from Astragali Radix (AR; Huang Qi), has been shown to have an effect of anti‐allergic dermatitis with unknown mechanism. This study aims to investigate the mechanism of calycosin related to tight junctions (TJs) and HIF‐1α both in FITC‐induced mice allergic contact dermatitis and in IL‐1β stimulated HaCaT keratinocytes. Th2 cytokines (IL‐4, IL‐5 and IL‐13) were detected by ELISA. The epithelial TJ proteins (occludin, CLDN1 and ZO‐1), initiative key cytokines (TSLP and IL‐33) and HIF‐1α were assessed by Western blot, real‐time PCR, immunohistochemistry or immunofluorescence. Herein, we have demonstrated that allergic inflammation and the Th2 cytokines in ACD mice were reduced significantly by calycosin treatment. Meanwhile, calycosin obviously decreased the expression of HIF‐1α and repaired TJs both in vivo and in vitro. In HaCaT keratinocytes, we noted that IL‐1β induced the deterioration of TJs, as well as the increased levels of TSLP and IL‐33, which could be reversed by silencing HIF‐1α. In addition, administration of 2‐methoxyestradiolin (2‐ME), a HIF‐1α inhibitor, significantly repaired the TJs and alleviated the allergic inflammation in vivo. Furthermore, TJs were destroyed by DMOG or by overexpressing HIF‐1α in HaCaT keratinocytes, and simultaneously, calycosin down‐regulated the expression of HIF‐1α and repaired the TJs in this process. These results revealed that calycosin may act as a potential anti‐allergy and barrier‐repair agent via regulating HIF‐1α in AD and suggested that HIF‐1α and TJs might be possible therapy targets for allergic dermatitis.